The effect of business regulations, property rights, and legal system on CO2 emissions: empirical evidence from the BRICS-T countries - Mahmut Unsal Sasmaz; Yilmaz Bayar; Yasin Galip Gencer (Humanities & Social Sciences Communications)
Abstract Global CO2 emissions have continued to rise, although the rate of increase has begun to slow down due to environmental measures implemented at both international and national levels. Therefore, the results of empirical studies on the drivers of CO2 emissions have been crucial for design of the appropriate environmental policies. This research article explores the interaction amongst business regulations, property rights, legal system, income, urbanization, and CO2 emissions in the BRICS-T countries for the 2000–2021 duration by means of the novel causality and cointegration tests sensitive to heterogeneity and cross-section dependence. The results of the causality test reveal a mutual interplay amongst business regulations, property rights, urbanization and CO2 emissions and a unidirectional causality from income to CO2 emissions. Furthermore, the results of the long-run analysis also indicate that improvements in legal quality and property rights decrease CO2 emissions while business regulations, real GDP per capita, and urbanization increase CO2 emissions. Therefore, improvements in property rights and the legal system are vital for decreasing CO2 emissions. However, negative environmental effects of market-oriented business regulations, income, and urbanization should be balanced by stringent environmental policies.